ARTICLE REVIEW : PERAN MANAJEMEN PEMASARAN DALAM MENINGKATKAN PENJUALAN - Sholihatin, Ifa; Kurniawan, Dedi; Rusdi, Atsilah; Feby, Selvi; Pertiwi, Ayu Hana; Kristin, Ersa (AMMER : JOURNAL OF ACADEMIC & MULTIDICIPLINE RESEARCH, 2023)
Business actors in increasing their sales will carry out an activity to market their products. The method used in this research is Systematic Literature Review. Marketers in increasing product sales are important in supporting the success of the company. With this, a marketer can improve sales promotions, determine strategies to increase consumer buying interest and use public relations in marketing. The conclusion of this article is marketing management in product sales can find out the needs and wants of consumers. Through sales promotions that can be done offline or online, it is expected to increase sales. Determining the chosen strategy, namely by distributing products from producers to consumers, can use the marketing mix strategy. To retain consumers to continue buying products, marketing management uses public relations as a liaison between companies and consumers in order to establish good relations and maintain consumer confidence to continue using the products offered, so that companies can achieve their goals, namely sales targets and gain profits.